The health care burden in rural Burkina Faso: Consequences and implications for insurance design - Fadima Yaya Bocoum; Michael Grimm; Renate Hartwig (Elsevier, 2018)
This paper maps the health care burden of households in rural Burkina Faso. More specifically we investigate the financial burden of health shocks and the manner in which households respond. Our data allows us to differentiate the burden of chronic illness and handicap, more frequent and recurring illnesses and episodes of severe illness, accident and mortality. We find that the burden of health shocks and health spending is high, ranging from one third of monthly non-medical consumption for the treatment of common infectious illnesses to almost three times the monthly non-medical spending in case of death of a household member. To cope, households deplete savings, sell livestock or reduce consumption. In case of severe shocks they are also heavily reliant on transfers from outside. Looking at the economic consequences of health shocks we find that illness of whichever type - severe, chronic or more common - reduces household consumption. Furthermore, households which suffered from a severe illness show significantly lower livestock holdings. Many of the health insurance schemes implemented in developing countries are not yet taking note of the burden of severe and chronic illness. However, in light of the universal health insurance coverage objectives of the Sustainable Development Goals (SDGs) it should be considered an area for future expansion. Keywords: Community based health insurance, Coping, Illness, Shocks, Burkina Faso